Zein-Curcumin Composite Edible Films for Intelligent Packaging: A Natural pH-Sensing Indicator to Monitor Sea Bream Freshness - Demirtas, Burcu; Keser, Beyza; Tural, Serpil; Gul, Latife Betul; Yilmaz, Ilay; Parlak, Mahmut Ekrem; Saricaoglu, Furkan Turker (Mdpi, 2025)
This study developed and characterized zein-based edible films enriched with curcumin as natural pH-sensitive indicators for monitoring fish freshness. Colorimetric films were prepared with different curcumin concentrations (1-7% wt) and evaluated for physicochemical, mechanical, optical, and antioxidant properties. Increasing curcumin content reduced water vapor permeability (0.085-0.110 gmm/m(2)hkPa), lowered water contact angles (<90 degrees), and enhanced hydrophilicity. Films exhibited high brightness, with decreased a* and increased b* values, while light transmission decreased, improving UV barrier properties. Colorimetric response (Delta E*) across pH 3-10 was more pronounced at higher curcumin levels, confirming pH-sensitivity. Antioxidant activity significantly increased with curcumin loading (up to 24.18 mol Trolox/g). Mechanical analysis revealed decreased tensile strength but improved elongation at break, bursting strength, and deformation, supported by SEM images showing more homogeneous, micro-porous structures at 7% curcumin. Zein films containing 7% (wt) curcumin (Z/CR7) were applied to gilthead sea bream (Sparus aurata) fillets stored at 4 degrees C for 13 days. Results showed lower TBARS and TVB-N values in Z/CR7 compared to the control, indicating delayed lipid oxidation and spoilage. Colorimetric changes in the films corresponded with fish freshness deterioration, providing a clear visual indicator. Microbiological results supported chemical findings, though antimicrobial effects were limited. Curcumin-enriched zein films demonstrated strong potential as intelligent, biodegradable packaging for real-time monitoring of seafood quality.
Keywords: curcumin; zein; edible films; pH indicator; intelligent packaging; fish freshness